Numerical Investigation of 2D Lid Driven Cavity using Smoothed Particle Hydrodynamics (SPH) Method - Mohamad Shukri , Zakaria (2011)
This paper describes the formulation of fluid equation in application of Smoothed Particle Hydrodynamics (SPH) and ability of meshfree SPH method to model lid driven cavity problem. Although the lid driven cavity problem are usually successfully solved using traditional Finite Difference Method (FDM), they are all depends on the mesh ability. This SPH method is relatively new approach in solving fluid flow problem. The SPH method can be used to discretize the Navier–Stokes equation that governs fluid flows. In the present study, the ability of the meshless SPH method are investigate in simulating the fluid flow which is in 2D lid driven cavity problem. The result of this problem using meshfree SPH method is compare to the solution done using meshing software Fluent with Reynold Number 1 and it shows that the SPH method give good comparison to the FDM method.